Application of drone technology to assess nitrogen status in oil palm (Elaeis guineensis Jacq.) - Hashim, Nurul Azmina (2018)
Drones, also known as unmanned aircraft vehicles (UAV), are pilotless aircraft that are controlled by computers or simple remote control. Recently, drones have been used in spraying operations over a wheat field in Xinghua, East China's Jiangsu province. The drone can be potentially used to detect the nutrient status of plants. Elaeis guineensis or commonly known as oil palm is the main industrial crop in Malaysia. The health and quality of oil palm need to be monitored frequently. Generally, nitrogen (N) status in plant plays a major role in crop productivity. The conventional assessment of N status is usually based on leaf and soil analysis which are highly costly and laborious. The capability of a drone is not fully explored for nutrient assessment in cropping systems. Its use to assess N status in oil palm is a plausible option to consider due to the large crop acreage and potential cost and time-saving. Therefore, the objective of this project is to assess the feasibility of using drone technology to assess N status in a young oil palm stand. This project is carried out at the commercial oil palm plantation in Negeri Sembilan and eBee MultiSPEC 4C is deployed as the drone equipment. For this project, 76 samples per ha are chosen and analysed for Normalized Difference Vegetative Index (NDVI), RGB, thermal imaging. Corresponding leaf and soil analysis are carried out. Both drone analysis and manual (leaf and soil) analysis are compared. Based on the result, there is significant correlation between nitrogen status in leaf and drone imagery indices over the study region.